In-situ determination of time-dependent alginate-hydrogel formation by mechanical texture analysis. (1st February 2019) - Stößlein, Sebastian; Grunwald, Ingo; Stelten, Johannes; Hartwig, Andreas
Highlights: A precise and fast measurement for alginate hydrogel formation with CaCl2 is proposed. The measurement principle is based on the gel inhomogeneity (core/shell). The method can supplement high temperature NMR analysis of G/M ratio. Abstract: Although alginate-based hydrogels are widely used, determining their mechanical properties and explaining their ability to form a hydrogel in situ remains a challenge. A new method of external gelation using calcium chloride (CaCl2 ) is proposed to quantify the formation of alginate hydrogel and its mechanical properties as well as to observe its temporal behaviour. To this end, small inhomogeneous alginate beads were formed, which comprised a shell and a core. The bead's shell consisted of calcium alginate hydrogel, while its core was sodium alginate sol. The beads were mechanically tested with a texture analyser to provide a detailed description of the structure. Different alginate samples could be clearly identified, and the M(mannuron)/G(guluron) acid ratios could be extrapolated quickly and easily from the test results if calibrated by NMR. This enables a fast and cost-effective characterisation of different alginates with regard to their composition and gel formation properties.